Kinematika Sendi Lengan Penari Bapang Malangan - Achmad Maulana Risky; Dadang Hermawan; Nurida Finahari (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2021)
Dancers experience various injuries, because dancing requires high intensity movements. Frequent injuries to dancers involve overuse of joints and muscles. The highest potential for injury is in the knee. However, in the Bapang Malangan Dance, the arms are the limbs that are often used in extreme movements. Thus the potential for injury can be high. This study focuses on the kinematics of arm movement of the Bapang Malangan Dance in relation to the possibility of injury. The research was carried out through analyzing image data resulting from the rendering of dance video footage, following a kinematics-based biomechanical framework and engineering dynamics. The results showed that the kinematic analysis of the Bapang dancer's arm was depicted only on the change in position because velocity and velocity could not be measured directly. Changes in the position of the Bapang dancer's arms can be depicted in graphic form through frame analysis of the transformed video files into image files. The arm joints that get a lot of weight are the shoulder and elbow joints, which in Bapang Malangan dancers have the potential to experience injury due to tugging and twisting. The complexities of movements and changes in dancer movements turn out to make it difficult to determine the speed and acceleration by analyzing the rendered images. A measuring instrument is needed that can directly measure arm movements when dancing. This tool must not use cables so as not to obstruct the dance movement. Keywords: biomechanic, kinematic, arm joint, dancer, Bapang Malangan